A Preliminary Study of the Effect of Quercetin on Cytotoxicity, Apoptosis, and Stress Responses in Glioblastoma Cell Lines - Magdalena Kusaczuk; Rafał Krętowski; Monika Naumowicz; Anna Stypułkowska; Marzanna Cechowska‐Pasko (2022)
A growing body of evidence indicates that dietary polyphenols show protective effects against various cancers. However, little is known yet about their activity in brain tumors. Here we investigated the interaction of dietary flavonoid quercetin (QCT) with the human glioblastoma A172 and LBC3 cell lines. We demonstrated that QCT evoked cytotoxic effect in both tested cell lines. Microscopic observations, Annexin V-FITC/PI staining, and elevated expression and activity of caspase 3/7 showed that QCT caused predominantly apoptotic death of A172 cells. Further analyses confirmed enhanced ROS generation, deregulated expression of SOD1 and SOD2, depletion of ATP levels, and an overexpression of CHOP, suggesting the activation of oxidative stress and ER stress upon QCT exposure. Finally, elevated expression and activity of caspase 9, indicative of a mitochondrial pathway of apoptosis, was detected. Conversely, in LBC3 cells the pro-apoptotic effect was observed only after 24 h incubation with QCT, and a shift towards necrotic cell death was observed after 48 h of treatment. Altogether, our data indicate that exposure to QCT evoked cell death via activation of intrinsic pathway of apoptosis in A172 cells. These findings suggest that QCT is worth further investigation as a potential pharmacological agent in therapy of brain tumors.